Usefulness of Heart Rate Variability to Identify the Risk of Falling in Huntington’s Disease - Terroba Chambi, Cinthia Jennifer (2019)
Objective: To evaluate the relationship between the HRV and the risk of falling in HD patients.Background: Huntington’s disease (HD) patients have a high prevalence of falls, on the other hand, autonomic nervous system dysfunction has been reported from early stages of the disease. However, there is lack of evidence regarding the relationship between heart rate variability (HRV) and falls in this population....